Influence of Wintertime Polar Vortex Variation on the Climate over the North Pacific during Late Winter and Spring - Kequan Zhang; Tao Wang; Mian Xu; Jiankai Zhang (Atmosphere, 2019)
The effects of wintertime stratospheric polar vortex variation on the climate over the North Pacific Ocean during late winter and spring are analyzed using the National Centers for Environmental Predictions, version 2 (NCEP2) reanalysis dataset. The analysis revealed that, during weak polar vortex (WPV) events, there are noticeably lower geopotential height anomalies over the Bering Sea and greater height anomalies over the central part of the North Pacific Ocean than during strong polar vortex (SPV) events. The formation of the dipolar structure of the geopotential height anomalies is due to a weakened polar jet and a strengthened mid-latitude jet in the troposphere via geostrophic equilibrium. The mechanisms responsible for the changes in the tropospheric jet over the North Pacific Ocean are summarized as follows: when the stratospheric polar westerly is decelerated, the high-latitude eastward waves slow down, and the enhanced equatorward propagation of the eddy momentum flux throughout the troposphere at 60° N. Consequently, the eddy-driven jet over the North Pacific Ocean also shows a southward displacement, leading to a weaker polar jet but a stronger mid-latitude westerly compared with those during the SPV events. Furthermore, anomalous anti-cyclonic flows associated with the higher pressure over the North Pacific Ocean during WPV events induce a warming sea surface temperature (SST) over the western and central parts of the North Pacific Ocean and a cooling SST over the Bering Sea and along the west coast of North America. This SST pattern can last until May, which favors the persistence of the anti-cyclonic flows over the North Pacific Ocean during WPV events. A well-resolved stratosphere and coupled atmosphere-ocean model (CMCC-CMS) can basically reproduce the impacts of stratospheric polar vortex variations on the North Pacific climate as seen in NCEP2 data, although the simulated dipole of geopotential height anomalies is shifted more southward.